Barriers and challenges of building maintenance management practices for public universities in Perak - Abdul. Rahman, Milatulsamshi; Hassin, Mohd Asrul; Abdul Rahman, Mohammad Ashraf; Zainal Adnan, Farah Nieza Natasha (UiTM Press, 2025)
This study investigates the barriers and challenges associated with building maintenance management practices at public universities in Perak, Malaysia. The research aims to identify maintenance teams' existing obstacles and determine the most critical factors hindering effective maintenance practices. This study used a quantitative methodology to identify the primary barriers and challenges that Public Universities in Perak face when implementing efficient building maintenance practices. One hundred questionnaires were distributed to maintenance management personnel from three (3) Public Universities in Perak. The questionnaire was developed using four (4) key barriers and challenges: maintenance management, technological issues, human resources, and financial constraints. A total of eighty-six (86) participants from three (3) public institutions successfully returned the questionnaire. The collected data is examined using Statistical Package for the Social Sciences, SPSS version28. Means and percentages were calculated to rank the factors based on their criticality level. Findings reveal that inadequate funding, insufficient skilled personnel, aging infrastructure, and lack of advanced Information and Communication Technology (ICT) tools significantly impact maintenance management practices. The study emphasises the need for comprehensive strategies to address these challenges, ensuring the safety and functionality of university facilities. The recommendations aim to enhance maintenance effectiveness, supporting the overall improvement of academic environments and operational sustainability